Co-Occurrence of Myeloid and Lymphoid Neoplasms: Clinical Characterization and Impact on Outcome. A Single-Center Cohort Study - Bucelli, Cristina; Fattizzo, Bruno; Cattaneo, Daniele; Giannotta, Juri Alessandro; Barbullushi, Kordelia; Pasquale, Raffaella; Barozzi, Enrico; Barbanti, Maria Chiara; Pettine, Loredana; Rossi, Francesca Gaia; Reda, Gianluigi; Cassin, Ramona; et al. (Frontiers in Oncology, 2021)
The co-occurrence of myeloid neoplasms and lymphoproliferative diseases (LPD) has been epidemiologically described, particularly in myeloproliferative neoplasms (MPN). However, the clinical features of these patients are poorly known. In this study, we evaluated a single-center cohort of 44 patients with a diagnosis of myeloid and LPD focusing on clinical features, therapy requirement and outcome. The two diagnoses were concomitant in 32% of patients, whilst myeloid disease preceded LPD in 52% of cases (after a median of 37 months,6-318), and LPD preceded myeloid neoplasm in 16% (after a median of 41 months,5-242). The most prevalent LPD was non-Hodgkin lymphoma (50%), particularly lymphoplasmacytic lymphoma (54.5%), followed by chronic lymphocytic leukemia (27%), plasma cell dyscrasias (18.2%), and rarer associations such as Hodgkin lymphoma and Erdheim-Chester disease. Overall, 80% of BCR-ABL1-negative MPN patients required a myeloid specific treatment, and LPD received therapy in 45.5% of cases. Seven subjects experienced a vascular events, 13 a grade >3 episode (9 pneumonias, 3 urinary tract infection, and 1 sepsis), and 9 developed a solid tumor. Finally, 9 patients died due to solid tumor (4), leukemic progression (2), infectious complications (2), and brain bleeding (1). Longer survival was observed in younger patients (p=0.001), with better performance status (p=0.02) and in the presence of driver mutations (p=0.003). Contrarily, a worse survival was significantly associated with the occurrence of infections (p<0.0001). These data suggest that in subjects with co-occurrence of myeloid and lymphoid neoplasms, high medical surveillance for infectious complications is needed, along with patient education, since they may negatively impact outcome.